Does a combination treatment of repetitive transcranial magnetic stimulation and occupational therapy improve upper limb muscle paralysis equally in patients with chronic stroke caused by cerebral hemorrhage and infarction?: A retrospective cohort study. Issue 24 (18th June 2021) - Tatsuno, Hisashi; Hamaguchi, Toyohiro; Sasanuma, Jinichi; Kakita, Kiyohito; Okamoto, Takatsugu; Shimizu, Masato; Nakaya, Naoki; Abo, Masahiro
Abstract : Abstract: The clinical presentation of stroke is usually more severe in patients with intracerebral hemorrhage (ICH) than in those with cerebral infarction (CI); recovery of stroke-related muscle paralysis is influenced and limited by the type of stroke. To date, many patients have been treated by neurorehabilitation; however, the changes in the recovery of motor paralysis depending on the type of stroke, ICH or CI, have not been established. This study aimed to determine this difference in improvement of upper extremity paralysis using 2-week in-hospital N ovE l intervention U sing R epetitive transcranial magnetic stimulation combined with O ccupational therapy (NEURO). We scrutinized the medical records of all patients with poststroke (ICH or CI) upper extremity muscle paralysis using Fugl-Meyer assessments (FMAs) who had been admitted to 6 hospitals between March 2010 and December 2018 for rehabilitation treatment. This was a multiinstitutional, open-label, retrospective cohort study without control patients. We evaluated the effects of NEURO on patients with CI and ICH by dividing them into 2 groups according to the type of stroke, after adjustment for age, sex, dominant hand, affected hand side, time since stroke, and prediction of recovery capacity in the upper extremity. The study included 1716 (CI [n = 876] and ICH [n = 840]) patients who had undergone at least 2 FMAs and had experienced stroke at least 6 months before. The type of stroke had no effect on the outcomes (changes in the FMA-upper extremity score, F [4, 14.0]  = 2.05, P  = .09, partial η 2  = 0.01). Patients from all 5 groups equally benefited from the treatment (improvement in FMA scores) according to the sensitivity analysis-stratified analysis ( F  = 0.08 to 1.94, P  > .16, partial η 2  < 0.001). We conclude that NEURO can be recommended for chronic stroke patients irrespective of the type of stroke.